Phagocytosis Effectivity Test of Phenylbutenoid Compounds Isolated from Bangle (Zingiber cassumunar Roxb.) Rhizome - CHAIRUL CHAIRUL; PRAPTIWI PRAPTIWI; SOFNIE MARUSIN CHAIRUL (Biodiversitas Journal of Biological Diversity, 2009)
This study was conducted to determine the immunostimulant activity of several phenylbutenoid derivatives isolated frombangle (Zingiber cassumunar Roxb) rhizome: [1] [(E)-4-(3’,4’-dimethoxyphenyl)but-3-en-1-ol], [2] [(E)-4-(2’,4’,5’ trimethoxyphenyl) but-3-en-1-ol] and [3] [(E)-4-(3’,4’,1-trimethoxyphenyl)but-3-en-1-ol]. Immunostimulant activity was done by stimulating macrophage cells of mouse peritoneum. The result showed that [(E)-4-(3’,4’-dimethoxyphenyl)but 3-en-1-ol] compound had highest immunostimulant activity (99.0%) compared to compound 2 (93.7%) and 3 (80.0%).Key words: Zingiber cassumunar Roxb, immunostimulant, phenylbutenoid derivative, [(E)-4-(3’,4’-dimethoxyphenyl)but-3-en-1-ol], [(E)-4-(2’,4’,5’-trimethoxyphenyl)but-3-en-1-ol]and [(E)-4-(3’,4’,1-trimethoxy phenyl)but-3-en-1-ol